The Renaissance - Brooks, Susie (Brooks, Susie. Inside art movements., 2020)
Presents a brief visual overview of the Renaissance art movement, covering topics like what characterized this movement and made its artists different from Middle Age artists and how and why governments and rulers would commission paintings from figures like Raphael and Da Vinci. Includes a timeline and glossary.